Evaluasi Atas Penerapan Sistem Online Payment Point Pos (SOPPOS) Dalam Kaitannya Dengan Efisiensi Kegiatan Operasional Pada PT Pos Indonesia (Persero) - Muanas, Muanas; Wijayantri, Anggi Citra (Jurnal Ilmiah Ranggagading (JIR), 2010)
This research was done to evaluate payment point online system in applying, reporting, and its role in supporting operational activities efficiency. The result of this research shows that PT. Pos Indonesia (persero) has applied well payment point online system (SOPPOS). Operational activities from front-end to PRD Jakarta 10000, where its daily reporting in the form of softcopy and SOPPOS media and monthly reporting in the form of hardcopy have been carried out routinely and on time. The result of evaluation shows that there is one thing that make payment point online system (SOPPOS) become more efficient and more effective than payment point manual system. Payment point online system is very efficient in using time and man-power. The problem is there is obstraction in applying payment point online system such as cutting of gateway connection. However there is deviation in activating server that should be done by supervisor, it rather be shifted to one of counter officials. It can destroy internal control function. Keywords : Payment Point Online System, Efficient Operation Activity.